N-Acetyl-3-aminopyrazoles block the non-canonical NF-kB cascade by selectively inhibiting NIK. Issue 6 (4th May 2018) - Pippione, Agnese C.; Sainas, Stefano; Federico, Antonella; Lupino, Elisa; Piccinini, Marco; Kubbutat, Michael; Contreras, Jean-Marie; Morice, Christophe; Barge, Alessandro; Ducime, Alex; Boschi, Donatella; Al-Karadaghi, Salam; et al.
Abstract : Resulting from hit-to-lead optimization, the aminopyrazole3a is a NIK inhibitor selective over 44 kinases. Abstract : NF-κB-inducing kinase (NIK), an oncogenic drug target that is associated with various cancers, is a central signalling component of the non-canonical pathway. A blind screening process, which established that amino pyrazole related scaffolds have an effect on IKKbeta, led to a hit-to-lead optimization process that identified the aminopyrazole3a as a low μM selective NIK inhibitor. Compound3a effectively inhibited the NIK-dependent activation of the NF-κB pathway in tumour cells, confirming its selective inhibitory profile.